Invasive fungal infection in children with hematologic malignancy - Gülhan, Belgin; Kanık-Yüksek, Saliha; Özkaya-Parlakay, Aslınur; Yaralı, Neşe; Tezer, Hasan; Özbek, Namık Yaşar (The Turkish Journal of Pediatrics, 2019)
Despite improvements in diagnosis and treatment, invasive fungal infection (IFI) is still a major cause of morbidity and mortality in immunocompromised patients. In patients with hematologic malignancy, the most invasive fungal infections are caused by Candida and Aspergillus fumigatus. This study was designed retrospectively to summarize data in pediatric patients with acute lymphoblastic leukemia (ALL) and acute myeloblastic leukemia (AML) including risk factors for IFI, epidemiological and clinical features and treatment choices involving combination therapy from January 2006 through December 2014. We analyzed the records of 154 pediatric patients (125 ALL and 29 AML) receiving chemotherapy for hematologic malignancy. During follow-up 60 IFI episodes were observed. IFI episodes were observed more common in AML, compared to ALL (p=0.002). Among 60 IFI episodes, eight were proven, seven were probable and 45 were possible IFI episodes. Galactomannan antigen was investigated in 37 IFI episodes and found positive in seven probable IFI episodes. Fungemia was detected in seven patients with proven IFI and the most common microorganism was non-albicans candida spp. The most common antifungal drug was fluconazole (14.8%). A total of 29 patients (48%) had received empirically liposomal amphotericin B and 10 patients (16.6%) had received caspofungin. Crude mortality was 10.3% and attributable mortality was 6.4% during the study period. Invasive fungal infections continue to be a major cause of morbidity and mortality in children with hematologic cancer. The most common isolated agent from hemoculture was non-albicans Candida spp.